Prevalence of Denture-Related Stomatitis in Edentulous Patients at a Tertiary Dental Teaching Hospital - Adam, Razia Zulfikar; Kimmie-Dhansay, Faheema (Frontiers in Oral Health, 2021)
Oral mucosal lesions can be uncomfortable and can result in a poorer oral health related quality of life. This can be seen especially in edentulous patients who are mostly elderly and have comorbid diseases such as Diabetes Mellitus, which can impair their ability to withstand oral infections. In South Africa, one of the most unequal countries in the world, almost 50% of the population is edentulous and this prevalence increases as age increases. The aim of this cross-sectional study was to determine the prevalence of denture-related stomatitis in subjects who presented to a tertiary institution in Cape Town, South Africa for new complete dentures and to determine the risk indicators associated with it. Categorical data was displayed as frequencies and percentages and a multiple adjusted logistic regression was used to determine associations between Candida and certain risk indicators. Three hundred and ninety-six folders of participants who received complete dentures were included in this study. The prevalence of denture-related stomatitis was 25.76% (n=102). Almost 75% (n=225) females and 72.63% (n=69) males had no denture-related stomatitis . The most common site for candidiasis in this population was the palate and tonsillar area (40.2%, n=41) and the least common site was the upper ridge (2.94%, n=3). %).Candidiasis, in edentulous patients are highly prevalent in this population and more needs to be done to prevent